Long-Lasting Analgesia With Transdermal Fentanyl: A New Approach in Rat Neonatal Research - Dutriez-Casteloot, Isabelle; Emmanuelli, Virginie; Wiart, Jean-François; Tavernier, Annabelle; Besengez, Capucine; Storme, Laurent; Houfflin-Debarge, Véronique (Frontiers in Pharmacology, 2022)
Background: With advances in neonatal care, management of prolonged pain in newborns is a daily concern. In addition to ethical considerations, pain in early life would have long-term effects and consequences. However, its treatment remains inadequate. It was therefore important to develop an experimental model of long-lasting analgesia for neonatal research. Materials and Methods: Experiments were performed in six groups of rats with transdermal fentanyl 0, 3, 12, 50, 100, or 200 μg/kg/h from second postnatal day (P2) until weaning. Assessment of analgesia was carried out at P21, with behavioral scores (ranging from 0 to 3) using a 4% formalin test. Plasma levels of fentanyl were determined by UPLC/TQD at P22. Growth rate was investigated. Results: Fentanyl 100 and 200 μg/kg/h reduced scores of formalin-evoked behavioral pain. They increased time spent in pain score 0 (8 min 55 s and 6 min 34 s versus 23 s in controls) as in low pain scores 1 and 2, and decreased time in the most severe pain score 3 (19 min 56 s and 17 min 39 s versus 44 min 15 s). Fentanylemia increased in a dose-dependent manner from 50 μg/kg/h (2.36 ± 0.64 ng/ml) to 200 μg/kg/h (8.66 ± 1.80 ng/ml). Concerning growth, no difference was observed except weaker growth from P17 to P22 with 200 μg/kg/h. Clinically, we noticed no visible side effect from 3 to 100 μg/kg/h. Concomitantly, 200 μg/kg/h was responsible for ophthalmological side effects with appearance of corneal bilateral clouding in 90% pups. No difference was observed between male and female rats. Conclusion: Altogether, results indicate that transdermal fentanyl 100 μg/kg/h is an efficient therapeutic for long-lasting analgesia in lactating pups. This new model provides a useful tool for protection and welfare, and future opportunity for studying long-term health consequences of sustainable neonatal analgesia.